In modern days hair is considered as an important tool of study in forensic science to solve complicated vetero-legal cases. The examination of hair from the crime scene is extremely important in the criminal investigation as hair is an appendage of the - Sarma, Munmun; Choudhury, Kamal B. D.; Singson, Athang; Ahmed, Jahan; Sarma, Nirmali (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
In modern days hair is considered as an important tool of study in forensic science to solve complicated vetero-legal cases. The examination of hair from the crime scene is extremely important in the criminal investigation as hair is an appendage of the skin and resist putrefaction; thus, is of an evidential value when other evidence is not available. The present investigation was undertaken to study the hair of few species of wild and semi-wild mammals e.g. Bengal tiger (Panthera tigris), Indian one horn Rhinoceros (Rhinoceros unicornis), Asian elephant (Elephas maximus), Mithun (Bos frontalis), Barking deer (Cervulus muntjac) and Yak (Bos grunniens), to find out the specificity of the hair to the animal-based on indices like color, length, an average diameter of the hair- shaft, cortico-medullary index, and cuticular scale pattern to develop baseline information to solve the vetero-legal cases. The present study revealed that the cuticular scale pattern of a tiger was coronal simple, imbricate crenate in rhinoceros, imbricate flattened in elephant, imbricate crenate in mithun, imbricate flattened in barking deer, and imbricate crenate in yak. The mean diameter of their shafts ( in µm) were found to be tiger 140 ± 0.417, rhinoceros 160 ± 1.199, elephant 200 ± 1.958, mithun 150 ± 2.665, barking deer 135 ± 1.864, and yak 150 ± 3.670. Therefore, a cumulative data derived from these indices are helpful to determine the species of animal they belong to.